The Intention to Use E-Commerce VS. Physical Shopping in the Post-Covid Policy in Indonesia - Amelya Pane-Citra; Suwanto Ade; Eliahannanti Firdha; Harianto V. Monica (Jurnal Syntax Admiration, 2023)
Customers' shopping behavior since the Covid-19 pandemic have changed due to post-covid social restriction in Indonesia. This research study behavior patterns to find out consumer shopping trends in Indonesia after Post-Covid policy as a reference for market players to grow business in online or offline stores based on drivers (UTAUT 2, herd behavior) dan barriers perspectives. The sample in this study was 487 respondents from the population of Indonesia, and sampling technique used in this research is Probability Sampling. The data was carried out by collecting questionnaires containing 51 items related to the variables in this study. The results show that Performance Expectancy, Habit, Imitating Others have a positive effect on E-commerce Intentions Variables and the Technology Fear factors has a negative effect towards Ecommerce Intention. In addition, the Privacy Risk Variable have a positive impact on the Physical Shop Intention Variable, while hedonic motivation factor has a negative impact on Physical Shop Intention. The result would have contribution for business owners to have more understanding on Indonesian market in order to develop business in e-commerce and physical stores.